2001
DOI: 10.1097/00010694-200109000-00001
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL COMPOSITION OF THE ORGANIC MATTER IN NEOLITHIC SOIL MATERIAL AS REVEALED BY CPMAS 13C NMR SPECTROSCOPY, POLYSACCHARIDE ANALYSIS, AND CuO OXIDATION

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…The ancient soil horizons exhibit lower value and chroma than their natural counterparts. A comparable result attributed to the high aromatic content in the archeological soil material was recently obtained by Schmid et al (2001) when examining the filling of Neolithic pits. In a previous study ) the darkness of german chernozemic soils increased with the content of black carbon.…”
Section: The Mineral Matrixsupporting
confidence: 77%
“…The ancient soil horizons exhibit lower value and chroma than their natural counterparts. A comparable result attributed to the high aromatic content in the archeological soil material was recently obtained by Schmid et al (2001) when examining the filling of Neolithic pits. In a previous study ) the darkness of german chernozemic soils increased with the content of black carbon.…”
Section: The Mineral Matrixsupporting
confidence: 77%
“…A similar result was found by Spielvogel et al (2004). Several studies have observed that soils darken with increasing content of charred organic C or aromatic C contents (Schmidt et al, 1999;Schmid et al, 2001;Knicker et al, 2006). Our results further indicate that grass-derived heavy fractions were darker than those with C 3 signature formed under Araucaria forest or shrubs with comparable aromatic C concentration ( Figure 5).…”
Section: Soil Organic Matter Signatures In Grassland With Long-term Fsupporting
confidence: 89%
“…Geochemical analyses of pit fillings in a Middle to Late Neolithic settlement near Munich (Münchshöfen Kultur, 4600-4200 BC), provided further evidence that pit fillings within prehistoric settlements were not similar to natural soils (Schmid et al, 2001). The black settlement pit fillings differed from A horizons of Phaeozems, when polysaccharide and lignin were analyzed by CPMAS 13 C NMR spectroscopy.…”
Section: Do Luvic Phaeozems Differ From Prehistoric Settlement Soils?mentioning
confidence: 98%